2013
DOI: 10.1177/1071100712464212
|View full text |Cite
|
Sign up to set email alerts
|

Infections With Pseudomonas Aeruginosa in Charcot Arthropathy of the Foot

Abstract: Level IV, retrospective case Series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This correlates with findings by another Australian study that demonstrated P. aeruginosa to be more common in chronic wounds [43] and may reflect colonisation of chronic wounds over time. Other studies had also previously found P. aeruginosa to be associated with poorer outcomes [53,54] which may be due to an ability to impair wound healing [55], although it remains unclear whether P. aeruginosa is truly a causative factor in poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This correlates with findings by another Australian study that demonstrated P. aeruginosa to be more common in chronic wounds [43] and may reflect colonisation of chronic wounds over time. Other studies had also previously found P. aeruginosa to be associated with poorer outcomes [53,54] which may be due to an ability to impair wound healing [55], although it remains unclear whether P. aeruginosa is truly a causative factor in poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment and reconstruction of Charcot feet remains a surgical challenge. Most cases exhibit atypical, multidirectional destruction and instability, often combined with major bone loss and ulceration with infection[ 7 ]. In addition, most patients have comorbidities and suffer from diabetes mellitus, nephropathy, and/or peripheral vascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Longer operative duration, hemoglobin A1c levels >7 mg/dl, and peripheral neuropathy elevate complication rates, especially regarding wound healing and infections[ 8 , 9 ]. Infections with P. aeruginosa in particular have been associated with poor outcomes[ 7 ].…”
Section: Introductionmentioning
confidence: 99%